Educação de jovens e adultos e implicações para gestão escolar: um panorama bibliográfico - Santana, Larissa dos Santos Ferreira de (2020)
This study aims to analyze the responses that Youth and Adult Education (YAE) brings to school management. As specific objectives: discuss how school management can contribute to ensuring the permanence of these students in the classroom in the learning process, taking as a reference what the theoretical production on the theme, works in works published in events and in periodicals , have you discussed these issues? To this end, a bulletin, based on the literature, will start with the characterization of the subject of YAE and its particularities, based on historical, legal and theoretical considerations, in addition to identifying specificities that interfere in their academic life, seeking to understand their difficulties socioeconomic context in which they are inserted, and thus identify the aspects that motivate them to return to classrooms in the YAE modality. The research methodology adopts the dialectical method defended by Marconi and Lakatos (2003) as capable of identifying contradictions and producing knowledge through the confrontation of ideas and reflections on them, also being characterized as exploratory, for investigating the theme, generating hypotheses about it and to clarify concepts so that ways are lost to contribute socially to the identified problems. The results of the research revealed that the management school is still little seen by students and teachers as a way to guarantee access, permanence and quality in YAE. The means for the election of managers in the Brazilian public school are still based on the nomination mechanisms, which weakens the democratic processes that can bring benefits to YAE and the school community in general. It was also identified that, in the school routine, management neglects YAE, as in many cases there is no presence of a manager during the night. It is concluded, therefore, that school management needs to be attentive to the needs and needs of YAE, in a participatory and democratic way, and that there is social mobilization for educational and social public policies that assist the subjects of YAE in their schooling process.